Disruption and continuity on telenovela with the surge of a new hybrid prime-time fictional serial: The super series. (June 2019) - Piñón, Juan
The Latin American telenovela genre has enjoyed a long-lasting hegemonic position in prime-time television across the region, and particularly within US Spanish-language television market. However, in the last several years, Spanish-language national television networks, as well as their prime-time telenovela product, are being challenged by the new digital and mobile media landscape. Television networks have deployed a variety of strategies to better accommodate to new audiences' consumption routines in a digital age. This article focuses on a particular moment of disruption – and continuity –, which has been a game changer for US Hispanic television and has transformed the face of fictional serial (telenovelas) in prime time. The surge in popularity of a telenovela subgenre originating in Colombia and widely adopted by US television corporations, known as narconovela, has transformed the telenovela genre/format, prompting industry professionals to initiate new institutional discourses aimed to mark these texts as super series, and in doing so labelling them as a new type of genre. Super series are an excellent case study for understanding the dialectic notion of disruption and continuity both in television studies and the television industry.